2012
DOI: 10.2147/cia.s33312
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative treatment using a radioelectric asymmetric conveyor as a novel tool in antiaging medicine: an in vitro beta-galactosidase study

Abstract: BackgroundBeta-galactosidase is the most widely used biomarker for highlighting the processes of cellular aging, including neurodegeneration. On this basis, we decided to test in vitro whether a set of rescuing/reparative events previously observed by us in subjects treated with radioelectric asymmetric conveyor (REAC) technology may also involve antagonism of a marker of aging-related degenerative processes, as assessed by a reduction in beta-galactosidase at the cellular level.MethodsHuman adipose-derived st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…REAC tissue optimization (TO) regenerative treatments (RGN) includes a set of treatment protocols 1 2 3 4 5 20 which are carried out by the ACP immersed in the medium of the cell culture or covering the treated area with ACP. The REAC TO-RGN has been administered 168 hours without interruption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…REAC tissue optimization (TO) regenerative treatments (RGN) includes a set of treatment protocols 1 2 3 4 5 20 which are carried out by the ACP immersed in the medium of the cell culture or covering the treated area with ACP. The REAC TO-RGN has been administered 168 hours without interruption.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies, conducted using the radio electric asymmetric conveyor (REAC) technology, have shown that this technology is able to induce neurogenic cell differentiation both in cultures of murine embryonic cells 1 and in differentiated human cells, such as fibroblasts 2 and adipocytes 3 . In addition, the REAC technology has been shown to effectively counteract cell aging 4 5 6 , a process often related to neurodegenerative diseases as Parkinson’s disease (PD). To better dissect and understand the potential of the REAC treatments in PD, we chose a PC 12 cellular model.…”
mentioning
confidence: 99%
“…Furthermore, REAC TO-RGN exposure proved effective in antagonizing the aging process in vitro 333435. Here, we show that REAC TO-RGN exposure also affected telomerase-dependent senescence mechanisms, by transcriptionally enhancing the expression of TERT, and counteracting telomere shortening.…”
Section: Discussionmentioning
confidence: 62%
“…For these reasons, researchers in recent years have been trying to dissect the epigenetic modifications involved in cellular aging, in an attempt to reverse stem cell senescence and achieve rejuvenation [32,33]. Physical stimuli such as electromagnetic fields have been largely applied to slow down cell senescence, by modulating cell polarity and the expression of the aging related markers, such as TERT, p16INK4, ARF, p53, and p21, together with the activity of beta-galactosidase [21,[34][35][36]. Moreover, other authors demonstrated that Rapamycin can inhibit mTOR and its signalling pathway, restoring both the self-renewal and the potency of stem cells [37].…”
Section: Discussionmentioning
confidence: 99%